Is Core Angular Momentum Key to the Giant Dynamo? - Klaus-Peter Schröder; Renada Konstantinova-Antova (Universe, 2022)
The pros and cons of core angular momentum dissipation into the convective envelopes of giants as a driver of giant activity is discussed in face of the observational evidence, which points to two ”magnetic strips“, in the HRD, where in the first, at the base of the RGB, activity of moderate mass stars is freshly started and rejuvenated in the second strip, ascending along the mid-AGB. It remains unclear, though, which depths the giant dynamo is operating. Both concentrations of active giants in the HRD are related to stellar evolution phases with core contraction and spin-up, and presumably the dissipation of angular momentum into the convective envelope above. At the same time, the latter has a small Rossby number by virtue of its increasing convective turn-over time—i.e., favourable conditions to run an alpha-omega dynamo. Since coronal X-ray emission appears to give an incomplete picture of stellar activity across the HR diagramme, we here focus on the observed chromospheric emissions across the giant branches and find good agreement with the magnetic field Zeeman-detections there. Stable evolution phases—solar-type main sequence stars with central hydrogen burning and moderate mass, central Helium burning K giants—by contrast demonstrate a decline in activity, apparently imposed by magnetic braking, as such stars are also slower rotators. In that sense, the observed picture of two magnetic activity strips across the HR diagramme could empirically be explained as an interplay of magnetic braking during the stable phase of core helium burning and supply by internal angular momentum during episodes of fast core contraction with core spin-up and angular momentum dredge-up, while meeting dynamo-friendly envelope conditions. At the same time, the sporadic external supply of angular momentum by the engulfment events of a planet, in the course of the evolutionary envelope expansion, may explain some cases of exceptional activity outside the here-described general picture.